Revisits: An Outline of a Theory of reflexive ethnography - Burawoy, Michael (American Sociological Review, 2003)
This paper explores the ethnographic technique of the focused revisit—rare in sociology but common in anthropology—when an ethnographer returns to the site of a previous study. Discrepancies between earlier and later accounts can be attributed to differences in: (1) the relation of observer to participant, (2) theory brought to the field by the ethnographer, (3) internal processes within the field site itself, or (4) forces external to the field site. Focused revisits tend to settle on one or another of these four explanations, giving rise to four types of focused revisits. Using examples, the limits of each type of focused revisit are explored with a view to developing a reflexive ethnography that combines all four approaches. The principles of the focused revisit are then extended to rolling, punctuated, heuristic, archeological, and valedictory revisits. In centering attention on ethnography-as-revisit sociologists directly confront the dilemmas of participating in the world they study—a world that undergoes (real) historical change that can only be grasped using a (constructed) theoretical lens.